М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
artembryzgin
artembryzgin
19.06.2021 04:11 •  Алгебра

Решить уравнения: cos (π/2 - t) - sin (π+t) = √2 sin x/3 = -1/2 5 cos^2 x + 6 sin x - 6 = 0 заранее, огромное ! : )

👇
Ответ:
мишка2283
мишка2283
19.06.2021
Cos (π/2 - t) - Sin (π+t) = √2
sint + sint = √2
2sint = √2
sint = √2/2
t = (-1)^(n)*arcsin(√2/2) + πn, n∈Z
t = (-1)^(n)*(π/4) + πn, n∈Z

2)  Sin x/3 = -1/2
x = (-1)^(n)*arcsin(-1/2) + πk, n∈Z
x/3 = (-1)^(n+1)*arcsin(1/2) + πk, k∈Z
x/3 = (-1)^(n+1)*(π/6) + πk, k∈Z
x = (-1)^(n+1)*(3π/6) + 3πk, k∈Z
x = (-1)^(n+1)*(π/2) + 3πk, k∈Z

3)  5 Cos^2 x + 6 Sin x - 6 = 0
5*(1 - sin^2x) + 6sinx - 6 = 0
5 - 5*(sin^2x) + 6sinx - 6 = 0
5*(sin^2x) - 6sinx + 1 = 0
D = 36 - 4*5*1 = 16
a)  sinx = (6 - 4)/10
sinx = 1/5
x = (-1)^(n)*arcsin(1/5) + πn, n∈Z
б)  sinx = (6 + 4)/10
sinx = 1
x = π/2 + 2πk, k∈Z 
4,8(73 оценок)
Ответ:
Alikhan666
Alikhan666
19.06.2021


1) sint+sint=√2

2sint=√2

sint=√2/2

x= П/4+2ПК  x=-3П/4+2ПК

2)sinx/3=-1/2

x/3=-П/6+2ПК       х/3=-5П/6+2ПК

х=-П/2+6ПК           х+-5П/2+6ПК

5cos²x+6sinx-6=0

5(1-sin²x)+6sinx-6=0

5-5sin²x+6sinx-6=0

-5sin²x+6sinx-1=0

5sin²x-6sinx+1=0

sinx=t

5t²-6t+1=0

D=9-5=4

t1=(3+2)/5=1  t2=(3-2)/5=1/5

sinx=1                     sinx=1/5

x=п/2+2ПК               х=(-1)^k arcsin(1/5)+Пк



4,7(8 оценок)
Открыть все ответы
Ответ:
srs777s
srs777s
19.06.2021
1) 3x² + 9 - 12x + x² = 0
4x² - 12x + 9 = 0
D = b² - 4ac = 144 - 16×9 = 0
x = -b/2a
x = 12/8
x = 1,5

2) 5x² + 1 - 6x + 4x² = 0
9x² - 6x + 1 = 0
D = b² - 4ac = 36 - 36×1 = 0
x = -b/2a
x = 6/18
x = 1/3

3) x² + 2x - 3 = 0
D = b² -4ac = 4 - 4×(-3) = 26 = 4²
x1 = ( - 2 + 4) / 2 = 1
x2 = ( - 2 - 4) / 2 = - 3

4) x² + 3x -4 = 0
D = b²- 4ac = 9 - 4×(-4) = 25 = 5²
x1 = ( - 3 + 5) / 2 = 1
x2 = ( - 3 - 5) / 2 = - 4

5) x² - 5x + 4 = 0
D = b² - 4ac = 25 - 4×4 = 9 = 3²
x1 =( 5 + 3) / 2 = 4
x2 = ( 5 - 3) / 2 = 1

6) x² - 4x + 3 = 0
D = b - 4ac = 16 - 4×3 = 4 = 2²
x1 = ( 4 + 2) / 2 = 3
x2 = ( 4 - 2) / 2 = 1

7) 2x² + x - 3x - 4 = 0
2x² - 2x - 4 = 0
x² - x - 2 = 0
D = b² - 4ac = 1 - 4×(-2) = 9 = 3²
x1 = ( 1 + 3) / 2 = 2
x2 = ( 1 - 3) / 2 = - 1

8) 2x² - 3x - 4x + 3 = 0
2x² - 7x + 3 = 0
D = b²- 4ac = 49 - 8×3 = 25 = 5²
x1 = ( 7 + 5) / 4 = 3
x2 = ( 7 - 5)/ 4 = 0,5
4,4(81 оценок)
Ответ:
Tinochka173
Tinochka173
19.06.2021
Условие:Решите уравнение:
а) 5х2 = 9х + 2;     б) -х2 = 5x - 14;
в) 6х + 9 = х2;       г) z - 5 = z2 - 25;
д) у2 = 520 - 576;  е) 15у2 - 30 = 22y + 7;
ж) 25р2 = 10p - 1; з) 299х2 + 100x = 500 - 101х2. ответ:а) 5х2 = 9х + 2; 5х2 - 9х - 2 = 0; D = 81 + 4 • 5 • 2 = 81 + 40= 121; х = (9±11)/10; х1 = -0,2; х2 = 2;
б) -х2 = 5x - 14; х2 + 5х - 14 = 0; D = 25 + 4 • 14 = 81; х = (-5±9)/2; х1 = -7; х2 = 2;
в) 6х + 9 = х2; х2 - 6х - 9 = 0; D = 36 + 4 • 9 = 36 + 36 = 72; х = (6±√72)/2; = 3 ± 3√2;
г) z - 5 = z2 - 25; z2 - z - 20 = 0; D = 1 + 80 = 81; х = (1±9)/2;; х1 = -4; х2 = 5;
д) у2 = 520 - 576; у2 - 52у + 576 = 0; D1 = 262 - 576 = 676 - 576 = 100; х = (26±10)/1; х1 = 16; х2 = 36;
е) 15у2 - 30 = 22y + 7; 15у2 -22у - 37 = 0; D = 112 + 37 • 15 = 676; х = (11±26)/15; х1 = -1; х2 = 37/15 = 2 7/15;
ж) 25р2 = 10p - 1; 25р2 - 10р + 1; D1 = 25 - 25 = 0; p = 5/25 = 1/5;
з) 299х2 + 100x = 500 - 101х2; 400х2 + 100х - 500 = 0; 4х2 + х - 5 = 0; D = 1 + 4 • 4 • 5 = 81; х = (-1±9)/8; х1 = -1 1/4; х2 = 1.
4,6(44 оценок)
Это интересно:
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ